Nonuniform Multiwavelet Sets and Multiscaling Sets. (1st February 2016) - Mittal, Shiva; Shukla, Niraj K.; Atlouba, Nadya A. S.
ABSTRACT: In this article, we study the theory of nonuniform minimally supported frequency multiwavelets and nonuniform multiscaling sets. A characterization of nonuniform multiwavelet sets is obtained which generalizes a result of Yu and Gabardo. After introducing a notion of generalized nonuniform scaling set, we obtain a characterization of nonuniform multiscaling sets associated with nonuniform multiresolution analysis having finite multiplicity. In addition, we provide a geometric construction to find families of symmetric nonuniform multiwavelet sets.